ROMANIAN RURAL AREAS DIVERSITY – TYPOLOGIES OF SUSTAINIBILITY - Rusu, Marioara (Economics of Agriculture, 2012)
Relatively new concept, sustainable development as economic development is providing the current consumer satisfaction without compromising or prejudicing those of future generations. The main objective of this paper is to identify similar developing structures in rural communities, using significant indicators of sustainability. Methodological approach included four steps: i) defining the rural space ii) selection of indicators of sustainability, what are specific for economic, social and environmental fingerprint; iii) integration and aggregation of indicators; iv) the grouping of communes - features six categories relatively homogeneous. This approach to classification of rural communities can be a model-based approach that could be a start in developing effective strategies for rural development.